Analisis Net Profit Margin (Npm) Dalam Meningkatkan Pertumbuhan Laba Pada Pt. Semen Indonesia (Persero) Tbk - -, Saqirah; Muniarty, Puji (Ekopem: Jurnal Ekonomi Pembangunan, 2023)
This study aims to analyze and find out how good Net Profit Margin is in increasing profit growth at PT. Semen Indonesia (Persero) Tbk. This type of research is descriptive with a quantitative approach and the research population is in the form of profit and loss financial statements from 1991-2021 (30 years) from PT. Semen Indonesia (Persero) Tbk. for the sample in this study, namely 10 years from the 2012-2021 period. Data collection methods are documentation and literature studies using purposive sampling. Data analysis in this study is descriptive analysis and statistical analysis using a simple test. Shows the results of research that the Net Profit Margin can not describe a good profit growth at PT. Semen Indonesia (Persero) Tbk